(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the socio-philosophical interpretation of poverty and its theoretical and methodological foundations. Poverty is examined not only as an economic issue but also as a manifestation of spiritual, cultural, and moral crisis. The author philosophically explores the relationship between poverty, human dignity, social justice, and equality. Furthermore, the methodological significance of sociological, anthropological, and axiological approaches in studying the phenomenon of poverty is discussed.